Long-term controlled in vitro release of FITC-dextran using polymer-based drug delivery systems manufactured by semi-solid extrusion 3D printing - Pohjola, Juuso; Jokinen, Mika; Soukka, Tero; Stolt, Mikael (Elsevier, 2026)
Controlled release drug delivery systems provide significant advantages over traditional therapeutic approaches by enabling continuous drug release over extended periods at a predetermined rate, thereby enhancing treatment efficacy and patient compliance. However, their performance is often limited due to the inability to account for individual patient characteristics. 3D printing of semi-solid inks has emerged as a promising method for the preparation of personalized medicine, addressing the need for customized designs and drug release properties. Despite the advantages of 3D printing, the commonly used materials and processing methods have demonstrated limited success in manufacturing of controlled release systems for macromolecule drugs, highlighting the need for further development. This study presents a method for creating macromolecule-releasing polymer-based drug delivery systems via semi-solid extrusion 3D printing. Fluorescein isothiocyanate-dextran model drug was encapsulated in PLGA microspheres, which were incorporated into extrudable Carbopol gel-based inks, either alone or blended with drug-free microspheres. Cylindrical models were printed at room temperature and exposed to solvent vapor to tailor the object porosity, followed by in vitro assessment of material degradation and drug release over three months. The results indicated that the system porosity significantly influenced the burst release and polymer degradation rate. Additionally, the drug release rate could be either accelerated, slowed, delayed, or entirely prevented by tailoring the ink composition and post-processing conditions. Given the growing interest in macromolecule drugs, the reported method demonstrates potential for the future development of controlled release systems for such molecules.